KEEFEKTIFAN MODEL CONNECTED DAN INTEGRATED DALAM PEMBELAJARAN IPS SMP DI KOTA YOGYAKARTA - Idrus idrus (Informasi, 2011)
This research aimed to: (1) analyze the differences in social studies learning achievement between the students using connected and integrated models and those using conventional model; and (2) analyze the hierarchy of the effect of the learning models  among the connected, integrated, and conventional. This experimental research employed a matching post-test comparison group design. The population of this research was National Standardized Schools of Junior Secondary Schools in Yogyakarta. The technique used for sample drawing was multistage sampling. In this research, the independent variable was the learning model which consisted of three categories: integrated, connected, and conventional models. The dependent variable was the mean score of students’ learning achievement in social studies subject. Data collection was done by means of an achievement test. Instrument validation was done by discriminating power and difficulty index, while the reliability was calculated by KR-20. The pre-requisite  test included normality and homogeneity tests. The normality test used Kolmogorov-Smirnov and the homogeneity test used Levene Test. Data were analyzed in one way anova analysis and continued with Scheffe comparison test on the significance level of 0.05. The results of the experiment show that there are  significant difference among the students’ learning achievement who used integrated, connected, and conventional models. The continued test using Scheffe ensured that the integrated model was more effective than the connected and conventional models, while the connected model was more effective in improving the students’ learning achievement in social studies subject compared with the conventional model. Therefore, the hierarchy of the effect of the learning models is first the integrated model followed by connected and conventional models. Key words: Connected, Integrated Models, Social Studies Learning